1969
DOI: 10.1021/ic50073a038
|View full text |Cite
|
Sign up to set email alerts
|

Transfer reactions involving boron. XX. Disproportionation reactions of alkyl-, alkoxy-, and haloboranes

Abstract: The solution redistribution equilibria of borane with alkylboranes, alkoxyboranes, haloboranes, and arylmercaptoboranes have been studied. The results obtained with the various systems are discussed individually and compared with each other and, when available, with gas-phase and other data appearing in the literature. The redistribution of trialkylboranes with borane in tetrahydrofuran produces a mixture of mono-, di-, and triatkylboranes and borane, the first two being the predominant products. Complicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 1 publication
(2 reference statements)
0
15
0
Order By: Relevance
“…[18] At this point two possible subsequent pathways of the monoalkoxyborane include: (a) reduction of two solvent molecules with formation of a trialkoxyborane via a dialkoxyborane, [18] (b) reaction with a second monoalkoxyborane to regenerate borane itself and to form a dialkoxyborane and subsequently a trialkoxy species (Scheme 4). [19] Monoalkoxyboranes are unstable compounds and readily undergo further transformations; therefore, the newly formed species should mainly be dialkoxy-or trialkoxyboranes. To test our hypothesis that alkoxyboranes are responsible for the unexpected stereochemical outcome during the hydroboration of 3,6-dihydro-2H-1,2-oxazine syn-1a a series of control experiments was performed.…”
Section: Hydroboration Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] At this point two possible subsequent pathways of the monoalkoxyborane include: (a) reduction of two solvent molecules with formation of a trialkoxyborane via a dialkoxyborane, [18] (b) reaction with a second monoalkoxyborane to regenerate borane itself and to form a dialkoxyborane and subsequently a trialkoxy species (Scheme 4). [19] Monoalkoxyboranes are unstable compounds and readily undergo further transformations; therefore, the newly formed species should mainly be dialkoxy-or trialkoxyboranes. To test our hypothesis that alkoxyboranes are responsible for the unexpected stereochemical outcome during the hydroboration of 3,6-dihydro-2H-1,2-oxazine syn-1a a series of control experiments was performed.…”
Section: Hydroboration Experimentsmentioning
confidence: 99%
“…Although we never obtained a 1:1 ratio as observed in the initial experiment with "degraded" borane-THF complex, our experiments clearly demonstrate that formation of alkoxyboranes is very likely the reason for the reduced stereoselectivity. Wojtkowski [19] had shown that 1:1 mixtures of alcohols and borane led to equilibria of dialkoxy-and trialkoxyborane species with values for the equilibrium constant K c = 2.9-7 in favour of the trialkoxy species for sterically less demanding alcohols and K c = 0.13-0.17 in favour of the dialkoxyborane species for tert-butyl alcohol. Given the facts, that monoalkoxyboranes are fairly unstable, that alkoxyboranes are significantly weaker reducing agents than borane itself, and that our hydroboration attempts with primary or secondary boranes such as thexylborane, disiamylborane, 9-BBN and catecholborane [14g] completely failed, we assume that in situ formed dialkoxyboranes are the key for shifting the ratio of diastereomers, but are not the reducing agents.…”
Section: Hydroboration Experimentsmentioning
confidence: 99%
“…1), and dialkoxyborane 5 could react with monoalkoxyborane 4 to yield trialkyl borate · THF complex 6 and borane · THF complex (Eqn. 2) [17]. Because no monoalkoxyborane 4 was detected, they only determined the equilibrium constant of Eqn.…”
Section: Scheme 1 Formation Of the Monoalkoxyborane · Oab Complexmentioning
confidence: 99%
“…7 Trialkoxyborane and borane are produced in a much slower redistribution reaction of dialkoxyboranes. 17, 19 With increasing steric demand this reaction becomes much slower. If the alkoxy group is tert-butoxy, the equilibrium is reached in THF only after more than one month at 25 ЊC.…”
Section: Kinetic Schemementioning
confidence: 99%
“…If the alkoxy group is tert-butoxy, the equilibrium is reached in THF only after more than one month at 25 ЊC. 19 Therefore, the redistribution of DB = bis(3,3dimethylbutan-2-oxy)borane can be neglected on the short timescale of the reaction of P. Semi-empirical calculations suggest that MB and DB, like borane, coordinate with a solvent molecule to form the complexes MB-T and DB-T in THF. The oxygen atom of the ketone couples to the boron atom in the reaction with the borane reagents.…”
Section: Kinetic Schemementioning
confidence: 99%